2019
DOI: 10.1101/564104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental plasticity and colonisation history in the Atlantic salmon microbiome: a translocation experiment

Abstract: Microbial communities associated with the gut and the skin are strongly influenced by environmental factors, and can rapidly adapt to change. Historical processes may also affect the microbiome. In particular, variation in microbial colonisation in early life has the potential to induce lasting effects on microbial assemblages. However, little is known about the relative extent of microbiome plasticity or the importance of historical colonisation effects following environmental change, especially for non-mamma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 55 publications
2
29
1
Order By: Relevance
“…These data corresponded broadly with increasingly negative NTI values among later lifecycle stages and suggest that a subset of host-adapted, taxonomically-related OTUs come to dominate the S. salar microbiome as it matures. The declining trend in OTU richness observed across lifecycle stages in our study is also consistent with observations that gut OTU richness declines with age in juvenile Atlantic salmon (45). As we noted in a previous study based on the wild salmon dataset (4), Mycoplasma sp.…”
Section: Discussionsupporting
confidence: 93%
“…These data corresponded broadly with increasingly negative NTI values among later lifecycle stages and suggest that a subset of host-adapted, taxonomically-related OTUs come to dominate the S. salar microbiome as it matures. The declining trend in OTU richness observed across lifecycle stages in our study is also consistent with observations that gut OTU richness declines with age in juvenile Atlantic salmon (45). As we noted in a previous study based on the wild salmon dataset (4), Mycoplasma sp.…”
Section: Discussionsupporting
confidence: 93%
“…appear to constitute small fractions of normal microbiomes and culture dependent techniques grossly overrepresent them [20]. Additional studies identified stress indicators [21] and probiotics candidates [22], both with conceivable applications in aquaculture and nature conservation, as well as the finding that captivity reduces the skin microbiome biodiversity [18,23,24]. Consistent salinity bioindicators were also recovered in an experimental system utilizing euryhaline fish [25].…”
Section: Introductionmentioning
confidence: 90%
“…Amazon River fish were also found to have high Alphaproteobacteria under certain physicochemical conditions [31]. In stark contrast, Gammaproteobacteria dominated the skin microbiome in wild S. salar fry [24], and also that of Silurus glanis, catfish caught in the wild [16]. Of the five instances, the catfish is the only strictly-freshwater inhabitant, but it lacks scales.…”
Section: Freshwater Fish-skin Microbiomementioning
confidence: 99%
“…Three species' microbiomes were tested for more than one tissue type; for example one species where the skin microbiome showed spatial structure but the gut microbiome did not (the fish Elacatinus prochilos) 0.5 was scored for presence and 0.5 for absence. salmon skin and gut microbiomes are strongly influenced by environmental conditions, but that developmental history also influences microbiome structure (Uren Webster et al, 2019). Similarly, returning adult Atlantic salmon in Canadian and Irish sites shared similar gut microbiomes to oceanic adult salmon from Greenland, but adult microbiomes were distinct from those of juvenile freshwater life stages (Llewellyn et al, 2015).…”
Section: Fishmentioning
confidence: 99%